1996
DOI: 10.1083/jcb.132.5.861
|View full text |Cite
|
Sign up to set email alerts
|

Movement of cortical actin patches in yeast.

Abstract: Abstract. In yeast, actin forms patches associated with the plasma membrane. Patch distribution correlates with polarized growth during the cell cycle and in response to external stimuli. Using green fluorescent protein fused to capping protein to image actin patches in living cells, we find that patches move rapidly and over long distances. Even patches in clusters, such as at the incipient bud site, show movement. Patches move independently of one another and generally over small distances in a local area, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
198
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(210 citation statements)
references
References 38 publications
(45 reference statements)
10
198
2
Order By: Relevance
“…Among them, six showed a partial colocalization with actin bodies (Arc15p, Arc18p, Arc35p, Arp2p, Crn1p, and Srv2p), and five others (Abp1p, Abp140p, Cap1p, Cap2p, and Sac6p) strictly colocalized with actin bodies. Abp1p and Cap1p/ Cap2p are ABPs detected only in actin patches (Drubin et al, 1988;Amatruda and Cooper, 1992;Doyle and Botstein, 1996;Waddle et al, 1996), Abp140p is a protein preferentially found in actin cables (Asakura et al, 1998;Yang and Pon, 2002), and Sac6p has been detected in both actin cables and patches (Drubin et al, 1988;Doyle and Botstein, 1996). To confirm those results and increase when necessary the GFP signal in quiescent cells, 3xGFP fusion proteins were constructed and shown to be functional (see Materials and Methods).…”
Section: Several Actin-binding Proteins Colocalize With Actin Bodiesmentioning
confidence: 77%
See 1 more Smart Citation
“…Among them, six showed a partial colocalization with actin bodies (Arc15p, Arc18p, Arc35p, Arp2p, Crn1p, and Srv2p), and five others (Abp1p, Abp140p, Cap1p, Cap2p, and Sac6p) strictly colocalized with actin bodies. Abp1p and Cap1p/ Cap2p are ABPs detected only in actin patches (Drubin et al, 1988;Amatruda and Cooper, 1992;Doyle and Botstein, 1996;Waddle et al, 1996), Abp140p is a protein preferentially found in actin cables (Asakura et al, 1998;Yang and Pon, 2002), and Sac6p has been detected in both actin cables and patches (Drubin et al, 1988;Doyle and Botstein, 1996). To confirm those results and increase when necessary the GFP signal in quiescent cells, 3xGFP fusion proteins were constructed and shown to be functional (see Materials and Methods).…”
Section: Several Actin-binding Proteins Colocalize With Actin Bodiesmentioning
confidence: 77%
“…Within these structures, protein exchange is very dynamic (Yang and Pon, 2002;Kaksonen et al, 2003), and the actin turnover in the filaments that form actin cables and patches is extremely rapid. Indeed, actin patches are very short-lived structures, the half-life of which is estimated to be 20 -40 s (Waddle et al, 1996). Consistently, in living cells, actin filaments rapidly disappear upon treatment with latruculin A (Lat-A), a drug that prevents G-actin polymerization (Ayscough et al, 1997).…”
Section: Actin Bodies Are Stable Structuresmentioning
confidence: 97%
“…One component of them, the capping protein (Cap2p), was fused to GFP and used as a reporter to monitor patch movement in living cells. Videomicroscopy revealed that changes in patch locations are due to movement of the patches and not to their disassembly and reassembly elsewhere [19].…”
Section: Cytoskeletonmentioning
confidence: 98%
“…Green fluorescent protein (GFP)-expressing cells were processed as described above with the exception that the spheroplasts were incubated for only 10 min at 37°C. Living spheroplasts were harvested by centrifugation and placed on microscope slide on a pad of 2% (wt/vol) agarose in PBS medium as described previously (Waddle et al, 1996). Cells were imaged using an Olympus AX70 Provis microscope equipped with a CoolSNAP HQ CCD camera controlled by IPlab Spectrum software (Scanalytics, Fairfax, VA).…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…One intriguing aspect of cortical actin patches is that they are highly motile (Doyle and Botstein, 1996;Waddle et al, 1996). The importance of actin patch motility in vivo is not yet understood, but there is evidence that motility may be initiated by Arp2/3 complex-nucleated actin polymerization (Winter et al, 1997;Kaksonen et al, 2003).…”
Section: Ultrastructure Of Cortical Actin Patches In Yeastmentioning
confidence: 99%